Stable Isotope Tracer Addition Reveals the Trophic Status of Benthic Infauna at an Intertidal Area Adjacent to a Seagrass Bed - Xu, Wenzhe; Dang, Yongxin; Cheung, Siu Gin; Zhang, Zhinan; Sun, Jun; Teng, Ankang; Shin, Paul K. S. (Frontiers in Marine Science, 2021)
Stable isotope tracer addition can enhance isotopic differences of primary producers for a wider food-web resolution than the use of natural abundance stable isotopes (NASI) alone, particularly in ecosystems where primary producers have similar NASI values. To investigate the food sources and trophic status of benthic infauna in an intertidal area near a Halophila minor seagrass bed within inner Tai Tam Bay, Hong Kong, China, a 15N addition experiment was conducted and results were compared with those from NASI data. Only benthic microalgae (BMA) were labelled by applying 15N-enriched NH4Cl to the sediment daily for the first 7 days during a 21-day study. In contrast to the NASI results, Bayesian mixing models based on the isotope tracer experiment suggested a larger dietary contribution of BMA for nematode Daptonema sp. and copepods, whereas a higher reliance on phytoplankton and seagrass detritus was noted for polychaete Neanthes sp.. Both NASI and isotope tracer addition, however, demonstrated that seagrass detritus was a major food source for nematode Spilophorella sp.. The present isotope tracer experiment also revealed a contrasting result of relatively lower contribution of meiofauna in the diets of carnivores/omnivores as compared to the results of NASI. This finding suggested that the isotope values in these consumers may have not reached an equilibrium with the added isotope in the study period. Thus, there is a need for applying NASI coupled with isotope tracer addition in the investigation of ecosystems in which primary producers have similar isotope values, especially in ecosystems with lower tissue turnover rates, in order for a more accurate determination of dietary contribution and trophic status of consumers in food-web study.